Agreement between community echocardiography and hospital echocardiography in patients suspected of having left ventricular systolic dysfunction. Issue 962 (12th December 2005) - Jeyaseelan, S; Goudie, B M; Pringle, S D; Donnan, P T; Sullivan, F M; Struthers, A D
Abstract : Background: Smaller echocardiography machines, when used in hospitals, are accurate for detecting left ventricular dysfunction and valvular disease. This paper assessed the detection of left ventricular dysfunction and of valvular disease in the community setting by a smaller machine. Aims: To measure the agreement in patients with suspected heart failure between community echocardiography and traditional echocardiography in the hospital in detecting left ventricular dysfunction and significant valve disease. Methods: Suspected heart failure patients were referred to one of the authors (SJ) for community echocardiography using a Siemens Cypress machine. The patients had a second echocardiogram in the hospital by another sonographer who was blinded to the results of the first echocardiogram. The reports of the two sonographers were assessed for agreement using κ statistics. Results: 458 patients had a community echocardiogram and 136 agreed to a second echocardiogram in the hospital. There was excellent agreement, κ = 0.87 (0.06 SE), for the detection of left ventricular dysfunction between community echocardiography and the hospital machine. The detection of significant valvular disease was good, κ = 0.75 (0.06) between the community echocardiogram and hospital machines. Conclusions: In suspected heart failure patients, community echocardiography gives comparable results to traditional hospital echocardiography for left ventricular dysfunction detection and for significant valvular disease detection.